2023
DOI: 10.3389/fmicb.2023.1110177
|View full text |Cite
|
Sign up to set email alerts
|

Exopolysaccharide-producing Lacticaseibacillus paracasei strains isolated from kefir as starter for functional dairy products

Abstract: Exopolysaccharides (EPS) produced by lactic acid bacteria are molecules of great interest for the dairy food industry. Lacticaseibacillus paracasei CIDCA 8339, CIDCA 83123, and CIDCA 83124 are potentially probiotic strains isolated from kefir grains whose EPS-production on MRS broth is dependent on incubation temperature. The aim of the present work is to evaluate the effect of fermentation temperature on the characteristics of EPS produced in milk by L. paracasei strains and the consequent impact on the rheol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 84 publications
0
1
0
Order By: Relevance
“…Lactobacillus strains such as Limosilactobacillus fermentum (Naghmouchi et al, 2020), Lactiplantibacillus plantarum L3 (Wang et al, 2023), Lactiplantiblacillus plantarum A3 and Lacticaseibacillus rhamnosus ATCC7469 (Li et al, 2023), Lacticaseibacillus paracasei (Bengoa et al, 2023), Lactiplantibacillus paraplantarum (Coimbra- Gomes et al, 2023), Lactobacillus rhamnosus B2-1 (Guo et al, 2023), and Limosilactobacillus fermentum (Paulino do Nascimento et al, 2022) are involved in the manufacture of several fermented foods for health-promoting effects (Nath et al, 2020;Widyastuti et al, 2021;Manzanarez-Quin et al, 2023) and acting as probiotics (Lynch et al, 2018;Lee et al, 2022;Coimbra-Gomes et al, 2023). Some strains of lactobacilli were reported to have probiotic activities that are useful in the prevention and treatment of gastro-intestinal disorders, such as rotavirus diarrhoea, antibiotic-associated diarrhoea, and travellers' diarrhoea, they can act as potential therapeutic agents to treat inflammatory bowel disease and irritable bowel syndrome (Kim et al, 2017;Levit et al, 2019;Krammer et al, 2021).…”
Section: Characteristics Of Beneficial Microbes In Palm Winementioning
confidence: 99%
“…Lactobacillus strains such as Limosilactobacillus fermentum (Naghmouchi et al, 2020), Lactiplantibacillus plantarum L3 (Wang et al, 2023), Lactiplantiblacillus plantarum A3 and Lacticaseibacillus rhamnosus ATCC7469 (Li et al, 2023), Lacticaseibacillus paracasei (Bengoa et al, 2023), Lactiplantibacillus paraplantarum (Coimbra- Gomes et al, 2023), Lactobacillus rhamnosus B2-1 (Guo et al, 2023), and Limosilactobacillus fermentum (Paulino do Nascimento et al, 2022) are involved in the manufacture of several fermented foods for health-promoting effects (Nath et al, 2020;Widyastuti et al, 2021;Manzanarez-Quin et al, 2023) and acting as probiotics (Lynch et al, 2018;Lee et al, 2022;Coimbra-Gomes et al, 2023). Some strains of lactobacilli were reported to have probiotic activities that are useful in the prevention and treatment of gastro-intestinal disorders, such as rotavirus diarrhoea, antibiotic-associated diarrhoea, and travellers' diarrhoea, they can act as potential therapeutic agents to treat inflammatory bowel disease and irritable bowel syndrome (Kim et al, 2017;Levit et al, 2019;Krammer et al, 2021).…”
Section: Characteristics Of Beneficial Microbes In Palm Winementioning
confidence: 99%
“…A notable example that extends this understanding is the EPS produced by Lacticaseibacillus paracasei strains isolated from kefir grains. Research has shown that the properties of these EPS vary with fermentation temperature, which not only affects their rheological properties in fermented dairy products, but also highlights their diverse functional capabilities in general [ 9 ]. In addition to lactobacilli, other polysaccharide-producing species have also been isolated from MK (e.g., Streptococcus thermophilus , Leuconostoc mesenteroides ) [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%